Prevalence of restless legs syndrome during the 2019 coronavirus disease pandemic in South Korea: A nationwide cross-sectional population-based study - Kim, Jiyoung; Kang, Kyung Wook; Kim, Keun Tae; Cho, Yong Won (Frontiers in Neurology, 2022)
Background The 2019 coronavirus disease (COVID-19) pandemic has been associated with a significant increase in sleep disorders. This study aimed to determine the prevalence of restless leg syndrome (RLS) and the effect of COVID-19 on RLS during the pandemic in Korea. Methods The National Sleep Survey of South Korea 2022 was employed in this study. This study was a large population-based web survey using a structural questionnaire of a four thousand representative sample of individuals aged 20–69 years in Korea. The survey was conducted between January 2022 and February 2022 during the COVID-19 pandemic. RLS was diagnosed using the Korean version of the paradigm of questions for epidemiological studies of RLS. Chronic persistent RLS was defined for individuals with RLS symptoms at least twice a week. Results Six hundred forty-nine (16.2%) and 172 (4.3%) patients were classified as having RLS and chronic persistent RLS, respectively. Female sex, being employed, the presence of COVID-19 vaccine-related adverse events, decreased sleep duration, the presence of EDS, and current treatment for insomnia were significantly associated with chronic persistent RLS. Conclusions During the COVID-19 pandemic, the prevalence of RLS and chronic persistent RLS in the adult Korean population was higher than that reported in previous studies.